Persistent babesiosis in a Rhesus macaque (Macaca mulatta) infected with a simian-human immunodeficiency virus - Liu, David X. (2014)
A rhesus macaque developed persistent babesiosis following inoculation with a simian-human immunodeficiency virus. Blood smears demonstrated intraerythrocytic piroplasms and rare Maltese cross forms. Babesia microti-like protozoa were confirmed by PCR and gene sequence. With using nonhuman primates as models for human diseases, infection and complications from Babesia should be monitored.